METHODS OF DETERMINATION OF POWER AND FUEL-ECONOMIC RATES OF MACHINE AND TRACTOR UNITS - A. G. Arzhenovskiy (Сельскохозяйственные машины и технологии, 2017)
One of the most important tendencies of increase in agricultural industry efficiency is improvement of methods and means for  determination of the main parameters of the machine and tractor  units (MTU). Every part of the MTU (an engine, a tractor and an  agricultural machine) has its own power characteristics which  combination makes one or the other mod of its operation. High- quality operation of MTU can be possible after study interaction of all these three main parts. So development of the methods of  determination of the unit parameters makes a big difference for  improvement of technical and economic parameters of the MTU.  Determination of connection between the separate parameters of the unit and the value of them using devices make it possible to solve  practical problems connected with improvement of the MTU operation: selection of the more productive combination of the units and their working modes; determination of the technically  reasonable production rate and consumption of the fuels and  lubricants oils; control of the technical condition of the engines,  tractors and agricultural machines, their correct adjustment. The  parameters characterizing the dynamic and economic qualities of the MTU are most important: ability rating of the engine and its fuel efficiency; ability rating of the tractor and its fuel efficiency; tractive  resistance of the machines in the unit. The operational methods of determination of the power and fuel-economic rates based on the  analysis of the parameters of the transition (dynamic) modes of  acceleration of the MTU at the instant increase of fuel supply are  represented in the research. Due to these methods the acquisition of the regulatory characteristic of an engine, the tractive characteristic of a tractor and find the draft of the agricultural machine during  operation are possible. In this case no need expensive equipment  using, essential expenditure of finances and time for preparation and carrying out of measurement.